SISTEM PENILAIAN KINERJA PEGAWAI DI RSUD SALEWANGAN MAROS - Hikmah Nurdin; Mukhtar Galib; Muharram Muharram (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
AbstractCurrently, Salewangan Maros Hospital began to design the development of employee performance assessment system. Salewangan Maros Hospital is still trying to find forms and mechanisms of assessment in accordance with the working climate and organizational culture in the hope that the employee performance assessment runs effectively and efficiently, therefore to support it is certainly needed accurate data and information about the existing performance assessment system so that it can be seen in terms of its advantages and weaknesses, which subsequently become a reference in the development of existing systems. In this study using qualitative data analysis and informants involved are those who have influence in the hospital Salewangan Maros Hospital. Based on the results of research and discussions can be concluded that in general the work performance assessment system of employees of Salewangan Maros Hospital has not run optimally, bias and subjectivity in the assessment is still high it can be seen from the method used, namely the rating scale and instruments used elements that are assessed only limited to attitude, behavior and personality alone have not touched on aspects of an employee's work achievement. Keywords : system, assessment, work achievement, employees